2005
DOI: 10.1103/physrevlett.94.187201
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioStudy of Mirages and Magnetic Interactions in Quantum Corrals

Abstract: The state of the art ab initio calculations of quantum mirages, the spin polarization of surface-state electrons, and the exchange interaction between magnetic adatoms in Cu and Co corrals on Cu(111) are presented. We find that the spin polarization of the surface-state electrons caused by magnetic adatoms can be projected to a remote location and can be strongly enhanced in corrals, compared to an open surface. Our studies give clear evidence that quantum corrals could permit one to tailor the exchange intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 20 publications
5
66
0
Order By: Relevance
“…Several applications of our method can be found in recent works. 11,22,23 We have found that the pair potential well depth is 0.6 meV which is in reasonable agreement with experiments. Therefore, we believe that the asymptotic equation ͑2͒ fitted to the experimental results properly describes the substrate-mediated interaction between Ce adatoms.…”
Section: Methods Of Calculationsupporting
confidence: 76%
See 1 more Smart Citation
“…Several applications of our method can be found in recent works. 11,22,23 We have found that the pair potential well depth is 0.6 meV which is in reasonable agreement with experiments. Therefore, we believe that the asymptotic equation ͑2͒ fitted to the experimental results properly describes the substrate-mediated interaction between Ce adatoms.…”
Section: Methods Of Calculationsupporting
confidence: 76%
“…12,20 The main contribution to the interaction energy at large adatom-adatom separations is well approximated by the single-particle energies alone. 12,21,22 We perform calculations of the interaction energies in the framework of the frozen potential approximation and use the Lloyd's formula for calculations of the single-particle energies. 21 As a benefit of this approach, calculations can be performed up to very large distances and very small interaction energies can be resolved.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Recently, by combining experimental results from cold atoms in a trap [16] and some universal arguments, an upper bound for the transition line from the quark gluon plasma phase (QGP) to the superconducting phase (SC) was proposed (T c ≤ 0.35E F ) [17,18]. To first approximation the Fermi-Energy E F is given by the chemical potential µ q .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Quantum corrals represent spectacular examples of confinement of surface localized states because of scattering at the boundaries of the artificially built structures. 1,3,4 Not only the nanostructure modifies the states which are already present at the surface, but new nanostructure-specific states can also emerge as has been demonstrated for, e.g., adatom chains, 5 nanoislands, 6 and adlayer structures. 7,8 Presently, the phenomena controlling the properties of confined states are rather well understood leading to their quantitative descriptions.…”
Section: Image Potential States Of Supported Metallic Nanoislandsmentioning
confidence: 99%